Pre-pregnancy body mass index and caesarean section in Andean women in Peru: a prospective cohort study - Giuliana Sanchez-Samaniego; Daniel Mäusezahl; Stella Maria Hartinger-Peña; Jan Hattendorf; Hector Verastegui; Günther Fink; Nicole Probst-Hensch (BMC, 2024)
Abstract Background During the last two decades, Caesarean section rates (C-sections), overweight and obesity rates increased in rural Peru. We examined the association between pre-pregnancy body mass index (BMI) and C-section in the province of San Marcos, Northern Andes-Peru. Methods This is a prospective cohort study. Participants were women receiving antenatal care in public health establishments from February 2020 to January 2022, who were recruited and interviewed during pregnancy or shortly after childbirth. They answered a questionnaire, underwent a physical examination and gave access to their antenatal care card information. BMI was calculated using maternal height, measured by the study team and self-reported pre-pregnancy weight measured at the first antenatal care visit. For 348/965 (36%) women, weight information was completed using self-reported data collected during the cohort baseline. Information about birth was obtained from the health centre's pregnancy surveillance system. Regression models were used to assess associations between C-section and BMI. Covariates that changed BMI estimates by at least 5% were included in the multivariable model. Results This study found that 121/965 (12.5%) women gave birth by C-section. Out of 495 women with pre-pregnancy normal weight, 46 (9.3%) had C-sections. Among the 335 women with pre-pregnancy overweight, 53 (15.5%) underwent C-sections, while 23 (18.5%) of the 124 with pre-pregnancy obesity had C-sections. After adjusting for age, parity, altitude, food and participation in a cash transfer programme pre-pregnancy overweight and obesity increased the odds of C-section by more than 80% (aOR 1.82; 95% CI 1.16-2.87 and aOR 1.85; 95% CI 1.02-3.38) compared to women with a normal BMI. Conclusions High pre-pregnancy BMI is associated with an increased odds of having a C-section. Furthermore, our results suggest that high BMI is a major risk factor for C-section in this population. The effect of obesity on C-section was partially mediated by the development of preeclampsia, suggesting that C-sections are being performed due to medical reasons.